ANTI-INFLAMMATORY EFFECT OF BETEL QUID ON MUCOSAL WOUND OF MALE WISTAR (RATTUS NOVERGICUS) RATS - PAMBAYUN, RINDIT; PUTRI, RAFIKA; SANTOSO, BUDI; WIDOWATI, TRI WARDANI; DEWI, SITI RUSDIANA PUSPA (International Journal of Applied Pharmaceutics, 2019)
Objective: True experimental in vivo with pre-test and post-test control group design was conducted at Animal House of Medical Faculty of Sriwijaya University Palembang and Biomedical Science Laboratory of Palembang, South Sumatera. Methods: Thirty rats were divided into five groups; three groups were treated with betel quid ointments at concentration of 5%, 10% and 20%, one group was positive control (hyaluronic acid) and last group was negative control (placebo). One-mm diameter of wound was made on lower lip mucosa of rats with cylinder diamond bur. Wound was induced with carrageenan. The number of neutrophils was counted on the first day and third day after treatment by using hematoanalyzer. Results: There was a significant decrease of the number of neutrophils for respective groups (p<0.05). Betel quid ointment of 10% and 20% concentration had similar effect to 0.2% hyaluronic acid (p>0.05). Conclusion: Betel quid has an anti-inflammatory effect on the mucosal wound of rats in a dose-dependent manner.